Dampak Reklamasi Pesisir Terhadap Kehidupan Sosial Ekonomi Nelayan di Batam - Noparia Sianipar; Nonis Sisrian; Roberta Bela (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
Coastal reclamation in Batam City is a development agenda aimed at increasing the economic value of coastal areas and supporting industrial growth. However, this reclamation has had a significant impact on the socio-economic lives of traditional fishermen who depend on the fisheries sector. This study uses a descriptive qualitative approach through literature review to examine the impact of reclamation on fish catches, household incomes, and the resulting social changes. The study results indicate that reclamation has resulted in a narrowing of fishing areas, a decrease in income of up to 40%, and social disorganization within fishing communities. Recommendations focus on protecting the socio-economic well-being of fishermen through inclusive and equitable policies, as well as increasing the empowerment of alternative economic sectors. This research is crucial as a basis for sustainable and socially responsible reclamation management.